'Thanks, but no thanks': Ethnographic Fieldwork and the Experience of Rejection from a New Religious Movement. (15th January 2016) - Burns, Emily
Abstract : Rarely do researchers publicly divulge their experiences of failure and rejection during fieldwork. Negotiations for access with members of new religious movements (NRMs) can be particularly fraught, especially for new researchers, who are embarking on a rite of passage with their first fieldwork experience. This article offers the author's experience of participant refusal during her doctoral research on a NRM in Australia in 2009, focused on the group's home birth practices. It provides an analysis of the methodological literature on access, rapport and the importance of a reflexive approach to one's positionality, and addresses the lack of scholarship on fieldwork rejection and failure. By engaging with the experience of rejection, this article argues that rather than a mere lack of rapport, it was the complex social and political context of the group, compounded by the politically charged topic of home birth, that generated the decline to participate. Using this experience as an example, this article argues that rather than embarrassment and shame, rejection and failure form part of the "non-data" of research practice, offering methodological and epistemological insights that come from a critical engagement with such experiences.